Performance of industrial wedge-anchors for pre-stressing BFRP bars: Experimental and numerical studies. (1st November 2020) - Motwani, P.; Perogamvros, N.; Taylor, S.; Laskar, A.
Abstract: The application of fibre reinforced polymer (FRP) bars as a pre-stressing element in concrete has shown excellent performance in the past few decades. Although, aramid, carbon and glass FRPs have been included in the ACI committee report, basalt fibre reinforced polymer (BFRP) bars have been excluded. This is due to insufficient research available on the application of BFRP as a pre-stressing element and availability of a reliable ready-to-use industrial anchor compatible with BFRP bars. This paper investigates the performance of industrial wedge-anchors to pre-stress BFRP bars. Anchor-efficiency and long-term relaxation of the bars have been estimated using load-cells and strain-gauges. The anchor-slips during the stressing of the bar have been monitored using digital image correlation technique and compared with linear-potentiometers. The test results showed an anchor-efficiency between 59% and 79% and indicated that the tested anchors can pre-stress the BFRP bars beyond the maximum initial pre-stress limit defined for FRP tendons as per ACI guidelines. The measured loss due to stress-relaxation after 1000 h was 12% and the data was extrapolated to predict million-hour stress-loss. The experimental data was utilised to develop a non-linear finite element model to perform parametric studies on the anchor system.